2019
DOI: 10.4081/mrm.2011.444
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in COPD patients and correlation with sputum and BAL cytology

Abstract: Background and aims: Anxiety and depression are common in patients with chronic obstructive pulmonary disease (COPD). The degree of lung function may not explain anxiety and depression. The aim of our study was to assess the psycholog- ical aspects of COPD, to test the BODE index (a composite score of body mass, obstruction, dyspnea and exercise capac- ity), and to evaluate the association between atypical cyto- logic findings of sputum, bronchoalveolar lavage (BAL) and the pyschological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Some previous studies identi ed impaired lung function (FEV 1 or GOLD severity) as a risk factor for depression [12,21,39]. However, other studies showed that FEV 1 %predicted was not independently associated with depression after adjusting for factors including respiratory symptoms and patient-reported outcomes [9,10,[40][41][42]. Our results showed that the relationship between lung function and clinical depression is relatively weak, FEV 1 %predicted was not associated with anxiety or depression after adjusting for CAT score and other confounders.…”
Section: Discussioncontrasting
confidence: 51%
“…Some previous studies identi ed impaired lung function (FEV 1 or GOLD severity) as a risk factor for depression [12,21,39]. However, other studies showed that FEV 1 %predicted was not independently associated with depression after adjusting for factors including respiratory symptoms and patient-reported outcomes [9,10,[40][41][42]. Our results showed that the relationship between lung function and clinical depression is relatively weak, FEV 1 %predicted was not associated with anxiety or depression after adjusting for CAT score and other confounders.…”
Section: Discussioncontrasting
confidence: 51%
“…7 Untreated and undetected anxiety and depressive symptoms may increase physical disability, morbidity, and health-care utilization. 8 While few published studies demonstrate that these disorders associated with COPD respond well to appropriate pharmacologic and non-pharmacologic therapy, only a small proportion of COPD patients with these disorders receive effective treatment. 7,9 Anxiety and depression are challenging to identify and treat because their symptoms often overlap with those of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' worsening anxiety and depression could be related to poor physical health, concerns about imminent death, persistent dyspnoea, severe functional limitation, dependency and burden on family members, and reduced exercise capacity. 18 19 Bueno et al found that LTOT in elderly patients is associated with poor self-image and leads to sadness and discouragement. 20 In a similar study, Hill et al showed that anxiety's prevalence is unrelated to using domiciliary oxygen.…”
Section: Open Accessmentioning
confidence: 99%